Against Youth Justice and Youth Governance, for Youth Penality - Phoenix, Jo (2016)
The main aim of this article is to provoke a debate about the ways in which state responses to youth crime are constituted as objects of knowledge in youth criminology. The article critiques two dominant approaches in youth criminology (youth crime governance and youth justice studies) in relation to the extent by which they are able to open the theoretical space to distinguish the conditions of possibility and analyse change. The main contention of the article is that in order to address these issues, the concept of ‘youth justice’ needs to be abandoned in favour of the development of a critical youth penality